2020
DOI: 10.1101/2020.06.17.157628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multiplex CRISPR interference tool for virulence gene interrogation in an intracellular pathogen

Abstract: In the absence of target cleavage, catalytically inactive dCas9 imposes transcriptional gene repression by sterically precluding RNA polymerase activity at a given gene to which it was directed by CRISPR (cr)RNAs. This gene silencing technology, referred to as CRISPR interference (CRISPRi), has been employed in various bacterial species to interrogate genes, mostly individually or in pairs. Here, we developed a multiplex CRISPRi platform in the pathogen Legionella pneumophila capable of silencing up to ten gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Lastly, the potential for Rho termination should be considered for biotechnological applications that require arrays with multiple spacers. Indeed, a recent study showed that including a boxA upstream of a 10-spacer CRISPR array substantially improves the efficiency of multiplexed CRISPRi in Legionella pneumophila ( Ellis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the potential for Rho termination should be considered for biotechnological applications that require arrays with multiple spacers. Indeed, a recent study showed that including a boxA upstream of a 10-spacer CRISPR array substantially improves the efficiency of multiplexed CRISPRi in Legionella pneumophila ( Ellis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, knockdown gradients can be achieved by expressing CRISPRi components from constitutive promoters of differing strengths (Qu et al., 2019), by using truncated spacers (Vigouroux, Oldewurtel, Cui, Bikard, & Teeffelen, 2018), or by systematically mutating the sgRNA to introduce mismatches between the spacer and target gene that reduce knockdown efficacy to a predictable extent (Hawkins et al., 2020). Finally, CRISPRi can be multiplexed to target several genes in the same cell by cloning arrays of sgRNAs with different spacers (Ellis, Kim, & Machner, 2020; Peters et al., 2016; Reis et al., 2019). These advantages suggest that CRISPRi will become a common tool for bacterial functional genomics in the near future.…”
Section: Introductionmentioning
confidence: 99%